Dynamism of Successive Childhood Bilingualism - Medved Krajnović, Marta (Array, 2006)
The paper presents two theoretical models of multilignual/bilingual development - Dynamic Model of Multilingualism (DMM) and Thresholds Theory (TT). The data from a case study of a successive Croatian (L1) - English (L2) bilingual development are presented in the light of DMM and TT. The author concludes that the mentioned models have a significant explanatory power but are not yet refined enough to present a multitude of aspects and interacting components in the development of successive childhood bilingualism